Friend and Foe. An Analysis of Expert Advice on Educating for Data Literacy in Journalism and the Creative Industries - Joke Hermes; Natalia Berger (VIEW Journal of European Television History and Culture)
Analysis of practical advice in regard of developing a data literacy course for students in higher education and for early-career professionals in interviews with 56 experts in data analysis, offered an unexpected shared story among the experts around the perception, affect and power of data. By attending to what data are felt to be and do to you unintentionally, the analysis delivered a new story of how to teach for data literacy. Rather than (only) focus on formal skills, it points to how building a relationship with data may help more students and young professionals become curious, critical and engaged while recognizing the strengths and the fickleness of data sets.